Jane's Patisserie celebrate! : bake every day special - Dunn, Jane (Baker) (Sourcebooks, 2024)
100 simple recipes to make every day a celebration, from the cross-platform sensation. From bestselling author Jane Dunn, the blogger and baker behind Jane's Patisserie, Celebrate! is packed with simple bakes, mouth-watering flavors and moreish treats that will make every day special. Good things come to those who bake!